Significant reduction in hospital admissions for acute exacerbation of chronic obstructive pulmonary disease in Hong Kong during coronavirus disease 2019 pandemic. (September 2020) - Chan, King Pui Florence; Ma, Ting Fung; Kwok, Wang Chun; Leung, Jackson Ka Chun; Chiang, Ka Yan; Ho, James Chung Man; Lam, David Chi Leung; Tam, Terence Chi Chun; Ip, Mary Sau Man; Ho, Pak Leung
Abstract: Background: Chronic respiratory diseases are risk factors for severe disease in coronavirus disease 2019 (COVID-19). Respiratory tract infection is one of the commonest causes of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). There has not been evidence suggesting the link between COVID-19 and AECOPD, especially in places with dramatic responses in infection control with universal masking and aggressive social distancing. Methods: This is a retrospective study to assess the number of admissions of AECOPD in the first three months of 2020 in Queen Mary Hospital with reference to the admissions in past five years. Log-linear model was used for statistical inference of covariates, including percentage of masking, air quality health index and air temperature. Results: The number of admissions for AECOPD significantly decreased by 44.0% (95% CI 36.4%–52.8%, p < 0.001) in the first three months of 2020 compared with the monthly average admission in 2015–2019. Compare to same period of previous years, AECOPD decreased by 1.0% with each percent of increased masking (p < 0.001) and decreased by 3.0% with increase in 1 °C in temperature (p = 0.045). The numbers of admissions for control diagnoses (heart failure, intestinal obstruction and iron deficiency anaemia) in the same period in 2020 were not reduced. Conclusions: The number of admissions for AECOPD decreased in first three months of 2020, compared with previous years. This was observed with increased masking percentage and social distancing in Hong Kong. We postulated universal masking and social distancing during COVID-19 pandemics both contributed in preventing respiratory tract infections hence AECOPD. Highlights: Admissions for COPD exacerbation decrease during COVID-19 period in Hong Kong. Decrease in COPD admission is observed with universal masking and social distancing. Universal masking and social distancing prevent respiratory tract infection. Masking reduces respiratory tract infection postulate to decrease COPD exacerbation.